Anti-inflammatory, Analgesic, and Cytotoxic Effects of The Phytexponent: A Polyherbal Formulation - Halvince O. Odira; Simon O. Mitema; Isaac M. Mapenay; Gervason A. Moriasi (SAGE Publishing, 2022)
The Phytexponent is used to treat pain and inflammation in complementary and alternative medicine practices; however, empirical data supporting its pharmacological efficacy and safety is scanty, hence the present study. We used the carrageenan-induced paw oedema and the acetic acid-induced writhing techniques to determine the anti-inflammatory and analgesic efficacies, respectively, of the Phytexponent in Swiss albino mice models. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay technique was used to investigate the in vitro cytotoxic effects of the Phytexponent in the Vero E6 cell line. The Phytexponent exerted significant ( P  < .05) anti-inflammatory effects in the carrageenan-induced paw oedema mouse model in a dose- and time-dependent manner, with significantly higher efficacy at 250 mg/Kg BW, than indomethacin (4 mg/Kg BW), in the first, second, and third hour ( P  < .05). Besides, the Phytexponent significantly reduced the acetic acid-induced writhing frequency in mice ( P  < .05), in a dose-dependent manner, depicting its analgesic efficacy. Notably, the Phytexponent (at doses: 125 mg/Kg BW and 250 mg/Kg BW) exhibited significantly higher analgesic efficacy than the Indomethacin ( P<. 05). Moreover, the Phytexponent was not cytotoxic to Vero E6 cells (CC 50 >1000 µg/ml) compared to cyclophosphamide (CC 50  = 2.48 µg/ml). Thus, the Phytexponent has significant in vivo anti-inflammatory and analgesic efficacy in mice models and is not cytotoxic to Vero E6 cell line, depicting its therapeutic potential upon further empirical investigation.